The Improve Recount Text Writing Skills By Using Picture Series At The First Year Students Of Akuntansi Keuangan Lembaga - Kadir, Kadir; Karyana, Sri; Sabarudin, Sabarudin; Yustiti, Yustiti; Marwa, Marwa (Jurnal Pendidikan Tambusai, 2024)
The aim of this research is to improve writing skills in recount text material using picture series as media with a problem based learning model at the first year students of Akuntansi Keuangan Lembaga SMK Negeri 1 Pendalian IV Koto, totaling 24 students. The method used in this research is Classroom action research consists of two cycles and each cycle consists of: planning, implementation, observation and reflection. The research shows that student learning outcomes have experienced a significant increase in the percentage of learning completeness, where in cycle I it was 83% and in cycle II it was 100%. % and the level of student activity in the learning process increased from 85.41% in cycle I to 94.44% in cycle II. Based on the results of this classroom action research, it can be concluded that the application of serial image media can improve the recount text writing skills at the first year students of  Akuntansi Keuangan Lembaga  SMK Negeri 1 Pendalian IV Koto.